Effect of chromium, vitamin C and vitamin E on blood sugar rats that induced by alloxan - Anugrah Linda Mutiarani (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2015)
Diabetes is a disease characterized by increasing blood sugar. People with diabetes continue to increasing number each year, so it needs better prevention of diabetes. Chromium is a cofactor in improving insulin action in the transfer of glucose into cells. In addition to chromium, vitamin C and vitamin E also plays a role in the prevention of diabetes, which is an antioxidant that can capture free radicals and prevent a chain reaction result in no cell damage. The aim o thi study was to analyzed the effect of chromium, vitamin C, and vitamin E on blood sugar rats that induced by alloxan. This research is an experimental laboratory. Sample were 20 male Wistar rats during 6 weeks. The independent variables consist of 5 treatment groups namely normal diet; normal diet + 1 g / day chromium; normal diet + 2 mg / day of vitamin C; the normal diet + 0.5 mg / day of vitamin ; a normal diet + 1 g / day chromium + 2 mg / day of vitamin C + 0.5 mg / day of vitamin E. The dependent variable is blood sugar levels. To know the differences of each treatment used statistical tests One Way ANOVA, followed by Tukey HSD Post Hoc test with p <0.05. There were significant differences in blood glucose (p = 0.000) between the control group and group 1, 2, 4, but between control group and  groups 3 showed no significant difference in blood glucose (p = 0.718). Chromium, vitamin C, and a mixture of chromium, vitamin C, vitamin E showed an effect on blood sugar, while vitamin E alone had no effect on blood sugar.